Technological Friction: A Comparative Analysis of Work-Life Balance between Information Technology and Administrative Professionals - Hamijaya, Prasis Damai Nursyam; Alif, Muhammad Ikhsan; Satyaninggrat, Luh Made Wisnu; Hidayat, Muhammad Afdelpiero (Jurnal Tekno Kompak, 2026)
The current dynamic global economic landscape positions human capital well-being as a primary strategic organizational priority, particularly amidst the high rates of mental exhaustion among young workers. Within the Indonesian technology industry ecosystem, this well-being crisis is further exacerbated by the flexibility paradox, where constant digital work demands frequently blur the strict boundaries between professional and personal life, ultimately triggering technostress. This study aims to empirically examine the direct effect of Work-Life Balance on employee Work Performance, evaluate the moderating role of technostress on this relationship, and analyze the differences in the moderation mechanism between IT Division (technical) and Non-IT Division (administrative) employees. This quantitative study utilized Partial Least Squares Structural Equation Modeling (PLS-SEM). Primary data were collected via questionnaires from a sample of 175 Generation Z and Millennial employees actively working in the technology industry, comprising 89 IT Division and 86 Non-IT Division workers. Instrument evaluation and hypothesis testing were conducted using the bootstrapping algorithm, followed by Multi-Group Analysis (MGA) to assess the significance of structural differences between these groups. The results demonstrate that Work-Life Balance has a positive and highly significant direct impact on employee performance achievement. In the moderation testing, the initial hypothesis was not supported as the interaction coefficient indicated a positive direction, contradicting theoretical predictions. Technostress conclusively demonstrated a buffering (strengthening) effect, wherein high stress levels actually amplify the urgency of Work-Life Balance as an essential psychological shield for employees to optimally maintain their operational performance standards. Furthermore, the MGA evaluation confirmed that this buffering effect operates significantly stronger among IT Division workers compared to Non-IT Division workers. This difference is primarily attributed to intense exposure to the always-on culture and operational workload expectations demanding full standby from the technical group. As a practical solution, management is recommended to implement a Digital Disconnect Protocol, design a tiered recovery framework specifically for the IT Division, and establish asynchronous work initiatives for the Non-IT Division. In conclusion, psychological well-being is an essential strategic necessity for maintaining sustainable productivity.